Optimizing tapered microfiber sensor design and simulation - Al-Askari, Shadi; Hamida, Belal Ahmed; Khan, Sheroz; Harun, Sulaiman Wadi (Asian Research Publishing Network (ARPN), 2016)
Refractive index sensors measure the evanescent field energy to sense various environmental parameters. Evanescent field-based sensors depend on the tapered area geometry which is one of the important factors for optimising the sensor performance as well as achieving better sensitivity and higher resolution. Tapering fabrication process needs to be controlled properly in order to achieve the optimal design. A two-dimensional model of the tapered sensor is proposed and simulated using Finite Element Analysis software, COMSOL Multiphysics. The light scattering phenomenon is visualized for taper and waist areas. The effects of the taper length, the waist length and the waist diameter have been explored in order to find the optimal geometries design. The model provides initial data to the designer to program and control the taper ration and the taper length the fabrication process in order to obtain the highest penetration depth at the highest resolution. The results show that the evanescent field is significantly high when the core diameter is close or below the wavelength. The output graph illustrates that when the tapering ratio decreases, more light propagate into the surrounding making the sensor more sensitive to the ambient changes. The simulation shows that the profile of the sensor can be fine-tuned by changing the tapering ratio of the waist and the length of the taper in order to obtain high performance, ultra-high-resolution evanescent field sensor.